2012
DOI: 10.7314/apjcp.2012.13.11.5371
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Tobacco Use Among Adolescents in North Kerala, India

Abstract: The present study was conducted to assess the prevalence and type of tobacco use among adolescents and also the reasons for the initiation of tobacco use amongst them. It was conducted in ten randomly selected schools in the Kannur district of Kerala state, India. A total of 3,000 school children participated. The study observed an overall prevalence of 5.5%. The prevalence observed among boys was 12% and none of the girls were tobacco users. Association between father's and friend's tobacco habits were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 7 publications
8
22
0
Order By: Relevance
“…In agreement with other studies (Sen et al, 2000;Golbasi et al, 2011;Muttappallymyalil et al, 2012), our results showed that peer pressure and peer influence is a major external factor that contributes to adolescents smoking. Similar to some studies (Kobus, 2003;, we also found that having a best friend who smokes and high peer pressure to smoke both increase the odds of being a susceptible never smokers and ever smokers.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with other studies (Sen et al, 2000;Golbasi et al, 2011;Muttappallymyalil et al, 2012), our results showed that peer pressure and peer influence is a major external factor that contributes to adolescents smoking. Similar to some studies (Kobus, 2003;, we also found that having a best friend who smokes and high peer pressure to smoke both increase the odds of being a susceptible never smokers and ever smokers.…”
Section: Discussionsupporting
confidence: 93%
“…14 Peer pressure has been found to be the most common reason for initiation of smoking even in Muttappallymyalil et al study. 15 Significant association was found between tobacco use among the students and their friends and family in the present study was similar to studies done by Bhojani et al and Muttappallymyalil et al (p=0.01). 10,15 Another study done by Mukherjee et al also showed similar association.…”
Section: Discussionsupporting
confidence: 82%
“…15 Significant association was found between tobacco use among the students and their friends and family in the present study was similar to studies done by Bhojani et al and Muttappallymyalil et al (p=0.01). 10,15 Another study done by Mukherjee et al also showed similar association. 16 In the present study, it is seen that tobacco use increases with age from 10% (12) among 13 years old to 33.33% among 16 years.…”
Section: Discussionsupporting
confidence: 82%
“…Similar to studies done by Mukherjee et al, Muttappallymyalil et al, we found that peers and family played a major role in initiation and continuation of smoking among the boys. 15,16 Predominance of peer pressure in schools is not be ignored when imparting education programs in schools for prevention of tobacco use. Role of skill based education for adolescents goes long way in building their strength to cope from peer pressure.…”
Section: Discussionmentioning
confidence: 99%